Sánchez Rebolledo, Antonio (Doctor) (2023)
Carta del Gral. Alvaro Obregón al Sr. Francisco Pérez, Director Gral. de los Ferrocarriles Nacionales de México, recomendando al Dr. Antonio Sánchez Rebolledo. Exp. S-14